Synthesis, characterisation and applications of new polyesters for drug delivery - Kakde, Deepak (2016)
In recent years, a number of reports have focused on the use of polyesters in drug delivery due to their intrinsic biocompatibility and biodegradability. In this thesis, aliphatic polyesters were synthesized by polycondensation reaction and ring opening polymerization reactions. The properties of the polymers and drug delivery potential of the resultant materials were evaluated. In the polycondensation reactions, a series of aliphatic polyesters of similar molecular weight were synthesized by reacting 1,10-decanediol with different ratios of succinic acid/phenylsuccinic acid and the effects of phenyl group side-chain substitution on polymer properties was investigated. A solvent-free melt polycondensation method using scandium (III) triflate as catalyst at an industrially relevant temperature (120 °C) was used. As the phenyl content increased, the polymers changed from semicrystalline to amorphous in state. The loading capability of polymers was checked by formulating nanoparticles containing coumarin 6 as a fluorescent dye analogue of active drugs. A polymer with a 70/30 ratio of succinic acid and phenylsuccinic acid showed the highest dye loading among the set of materials synthesised. This polymer was found to be degradable over time under selected experimental conditions. Amphiphilic block co-polymers from the PluronicTM class were used to stabilize, in PBS, nanoparticles formed from these polyesters by nanoprecipitation routes. The metabolic activity, cell membrane integrity and lysosomal functions of C3A cells dosed with the polymers were determined to observe the cytocompatibility of the highest dye-loaded nanoparticles. Activity relative to undosed C3A cells was retained at more than 80% in the all of the assays. Imaging of Pluronic coated and uncoated nanoparticles in C3A cells suggested that both types of the nanoparticles were endocytosed in the early stage of the study (within 10 min). The internalization of nanoparticles was increased progressively over the study time. These results indicated the possible utility of the selected polymers in diagnostic and delivery applications. Ring opening polymerization (ROP) reactions were used for the synthesis of a diblock (mPEG-b-PεDL) and a triblock (PεDL-b-PEG-b-PεDL) copolymer from a seven membered ε-decalactone (ε-DL) monomer obtained from renewable sources. A diblock (mPEG-b-PεDL) copolymer was compared with structurally similar mPEG-b-PCL copolymer synthesized via ROP of ε-caprolactone (ε-CL) monomer, which can be considered as a non-renewable monomer. A six membered δ-decalactone (δ-DL) was also used for the synthesis of a diblock copolymer (mPEG-b-PδDL) to compare the reaction kinetics and properties of the copolymers. The copolymers were prepared via bulk polymerisation using 1,5,7-Triazabicyclo[4.4.0]dec-5-ene (TBD) as a metal-free catalyst to replace the conventionally used stannous octoate [Sn(Oct)2]. A higher polymerization efficiency was achived with TBD compared to Sn(Oct)2 catalyst. However, a notable difference in the reaction temperature required for ε-DL and δ-DL polymerization was observed. The comparison with a structural analogue, i.e. ε-CL, demonstrated that the ε-DL polymerization was inhibited due to the presence of the alkyl chain of ε-DL monomer. However, a higher reaction time (12 h for TBD and 24 h for Sn(Oct)2) in CROP of ε-DL was addressed by using microwave based ring opening polymerization (MROP) reaction. The MROP was adopted as a ‘green’ and cheap heating method alternative to conventional heating (CROP) for the synthesis of mPEG-b-PεDL diblock copolymers using TBD as a catalyst. All the reactions were conducted in bulk. The MROP was designed based on the dielectric properties of all the reacting materials, as it was found that ε-DL monomers showed good absorption of MW radiation (tanδ>0.5). Accordingly, MROP resulted in a higher rate of ε-DL polymerization compared to CROP but comparison of the synthesis of mPEG-b-PCL copolymer by MROP indicated that the presence of the alkyl chain in ε-DL monomer significantly reduced the rate of polymerization. The synthesized mPEG-b-PεDL copolymer was investigated as a potential drug delivery vehicle for solubilization and controlled delivery of indomethacin. The indomethacin loading and release from mPEG-b-PεDL micelles (amorphous core) was compared against well-established mPEG-b-PCL micelles (semicrystalline core). The drug-polymer compatibility was also determined through a predictive computational approach to access the drug solubilisation (or drug loading) into hydrated micelles. The micelles were prepared by solvent evaporation method and characterized for size, morphology, indomethacin (IND) loading and release. Both of the micelle formulations showed a uniform distribution of spherical micelles with size <60 nm. However, a significantly higher size of empty mPEG-b- PεDL micelle was observed compared to mPEG-b-PCL micelles. A higher compatibility of the drug was predicted with PCL core as determined by modified Flory-Huggins interaction parameters (sp) using the Hanson solubility parameter (HSP) approach. The compatibility of the drug was determined for both of the segments (hydrophilic and hydrophobic) of the copolymers and found to be in the order of sp (PεDL)> sp (mPEG)> sp (PCL). The predictions suggested that more IND should encapsulate within the micelles with PCL core compared to PDL core, but the IND loading experiments revealed an overall higher loading in PεDL core (6.55 wt%) compared to PCL core (5.39 wt%) (P < 0.05, unpaired student’s t-test). However, consideration of the IND loading per unit volume of the micelles revealed that the PCL cored micelles was able to load 1.5 times more compared to the PεDL cored micelles. This result illustrated the higher compatibility of the IND with PCL core in accordance with the solubility parameter calculations. These data also suggested that the overall higher IND loading in PεDL core was attributable to the amorphous nature of the core which increased the core volume by 1.81 times compared to the PCL core. Drug release studies showed the sustained release pattern from both of the micelle systems although the semicrystalline PCL core (80% drug release in 110 h) was able to release the drug for a longer period compared to PεDL core (80% drug release in 72 h). Cell viability tests demonstrated the cytocompatibility of the mPEG-b-PεDL polymer. The micelles were internalized effectively in the early stages of the study and progressively increased with time. The results of the present thesis suggested that novel aliphatic polyester can be good candidates for the drug delivery applications and further studies can explore the possible applications of these polymers in the biomedical field.